2003
DOI: 10.1021/ja028710n
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Hydrogen Bond Lengths and Reduction Potentials in Clostridium pasteurianum Rubredoxin

Abstract: 15N NMR hyperfine-shift data were collected for wild-type and site-specific mutant (V44I, V44A, and V44G) Clostridium pasteurianum rubredoxins in the oxidized state. Whereas most of the (15)N NMR signals did not exhibit large systematic changes upon mutation of residue 44, the signal from the backbone nitrogen of residue 44 itself (arrows) shifted by approximately 400 ppm. These shifts were used to determine the lengths of the hydrogen bond between the backbone amide of residue 44 and the side-chain sulfur of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 19 publications
0
45
1
Order By: Relevance
“…These hydrogen bonds are purported to serve a dual purpose: they tune the cofactor E m as well as define ET pathways [65][66][67]. Markley and coworkers reported a 15 N NMR study of mutants of Val44 in Clostridium pasteurianum rubredoxin in which the hydrogen bond from the backbone amide at position 44 to the iron-ligating Cys42 varies systematically [68,69]. In these variants, no significant changes are noticed in the lengths of other hydrogen bonds.…”
Section: Rubredoxinsmentioning
confidence: 99%
“…These hydrogen bonds are purported to serve a dual purpose: they tune the cofactor E m as well as define ET pathways [65][66][67]. Markley and coworkers reported a 15 N NMR study of mutants of Val44 in Clostridium pasteurianum rubredoxin in which the hydrogen bond from the backbone amide at position 44 to the iron-ligating Cys42 varies systematically [68,69]. In these variants, no significant changes are noticed in the lengths of other hydrogen bonds.…”
Section: Rubredoxinsmentioning
confidence: 99%
“…Investigations of thermally induced unfolding of CpRd showed that loss of the metal ion immediately precedes formation of the (apparently) unstructured apoRd [19], but that Fe(SCys) 4 site stability does not control the thermostability of the native folded structure [20]. Engineered V ↔ A exchanges of residue 44, which forms an N-H…S hydrogen bond to one of the ironcoordinating Cys residues, significantly raised and lowered the respective stabilities of the Fe(SCys) 4 sites in CpRd and PfRd [21][22][23][24] but had only minor effects on the thermal stabilities of the folded holoRds. Thiophilic metal ions (Cd II , Zn II ) can directly and isomorphically displace iron from the native Fe II (SCys) 4 site of CpRd under nondenaturing conditions and without unzipping of the β-sheet [25].…”
Section: Introductionmentioning
confidence: 99%
“…The 15 N chemical shifts can resolve changes in H-bond distances on the order of 0.01 Å (19). Recently, an NMR study of a set of CpRd mutants revealed that electron delocalization onto the nitrogen of residue 44 varied with side-chain substitutions at this residue in a way that tracked changes in the reduction potential of the protein (21). This result has prompted us to carry out a comprehensive analysis of all six Fe-S⅐⅐⅐⅐⅐H N H-bonds of CpRd in a series of 10 sequence variants in their oxidized (Fe III ) and reduced (Fe II ) states.…”
mentioning
confidence: 99%